Iron deficiency is related to lower muscle mass in community‐dwelling individuals and impairs myoblast proliferation - Joanna Sophia J. Vinke; Alan R. Gorter; Michele F. Eisenga; Wendy A. Dam; Peter van derMeer; Jacob van denBorn; Stephan J.L. Bakker; Martijn F. Hoes; Martin H. deBorst (Wiley, 2023)
Abstract Background Loss of muscle mass is linked with impaired quality of life and an increased risk of morbidity and premature mortality. Iron is essential for cellular processes such as energy metabolism, nucleotide synthesis and numerous enzymatic reactions. As the effects of iron deficiency (ID) on muscle mass and function are largely unknown, we aimed to assess the relation between ID and muscle mass in a large population‐based cohort, and subsequently studied effects of ID on cultured skeletal myoblasts and differentiated myocytes. Methods In a population‐based cohort of 8592 adults, iron status was assessed by plasma ferritin and transferrin saturation, and muscle mass was estimated using 24‐h urinary creatinine excretion rate (CER). The relationships of ferritin and transferrin saturation with CER were assessed by multivariable logistic regression. Furthermore, mouse C2C12 skeletal myoblasts and differentiated myocytes were subjected to deferoxamine with or without ferric citrate. Myoblast proliferation was measured with a colorimetric 5‐bromo‐2'‐deoxy‐uridine ELISA assay. Myocyte differentiation was assessed using Myh7‐stainings. Myocyte energy metabolism, oxygen consumption rate and extracellular acidification rate were assessed using Seahorse mitochondrial flux analysis, and apoptosis rate with fluorescence‐activated cell sorting. RNA sequencing (RNAseq) was used to identify ID‐related gene and pathway enrichment in myoblasts and myocytes. Results Participants in the lowest age‐ and sex‐specific quintile of plasma ferritin (OR vs middle quintile 1.62, 95% CI 1.25-2.10, P < 0.001) or transferrin saturation (OR 1.34, 95% CI 1.03-1.75, P = 0.03) had a significantly higher risk of being in the lowest age‐ and sex‐specific quintile of CER, independent of body mass index, estimated GFR, haemoglobin, hs‐CRP, urinary urea excretion, alcohol consumption and smoking status. In C2C12 myoblasts, deferoxamine‐induced ID reduced myoblast proliferation rate (P‐trend <0.001) but did not affect differentiation. In myocytes, deferoxamine reduced myoglobin protein expression (−52%, P < 0.001) and tended to reduce mitochondrial oxygen consumption capacity (−28%, P = 0.10). Deferoxamine induced gene expression of cellular atrophy markers Trim63 (+20%, P = 0.002) and Fbxo32 (+27%, P = 0.048), which was reversed by ferric citrate (−31%, P = 0.04 and −26%, P = 0.004, respectively). RNAseq indicated that both in myoblasts and myocytes, ID predominantly affected genes involved in glycolytic energy metabolism, cell cycle regulation and apoptosis; co‐treatment with ferric citrate reversed these effects. Conclusions In population‐dwelling individuals, ID is related to lower muscle mass, independent of haemoglobin levels and potential confounders. ID impaired myoblast proliferation and aerobic glycolytic capacity, and induced markers of myocyte atrophy and apoptosis. These findings suggest that ID contributes to loss of muscle mass.